Application of fuzzy analytic hierarchy process for contractor selection problem / Nur Syuhaila Abdul Rashid, Nur Amirah Mohd Amin and Nor Faradilah Mahad - Abdul Rashid, Nur Syuhaila; Mohd Amin, Nur Amirah; Mahad, Nor Faradilah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Choosing the best contractor for services in the manufacturing company is one of the most important things in decision making processes. Nevertheless, it is a complex issue since the selection of best contractor is usually a multi criteria decision making problem. Thereby, the decision maker's knowledge is often vague and inaccurate. The objective of this study is to select the best maintenance contractor for a computer hard disk drive manufacturer and data storage company using Fuzzy Analytic Hierarchy Process (FAHP) method. The process of evaluating and selecting the best contractor will be based on multiple criteria that are often in conflict. Five criteria which are price (C1), past performance (C2), technical skills (C3), availability (C4) and financial stability (C5) of the contractors were used to select the best contractor from a list of alternatives (A1, A2, A3 and A4) provided by the decision makers. Throughout this study, the result shows that C3 is the most preferred criterion and the ranking order is C3 ≻ C2 ≻ C1 ≻ C4 ≻ C5. Simultaneously, the ranking order for alternative is A4 ≻ A3 ≻ A2 ≻ A1 as contractor A4 is selected as the best contractor to handle the machinery maintenance support for the company. Overall, the proposed FAHP method is beneficial as it allows the decision maker(s) to use their judgments are in the form of linguistic variables in selecting the most preferable alternative or option based on the existing multiple criteria.